The impact of Indonesia's decentralized education on vocational skills and economic improvement of students - Ari Setiawan; Dedek Andrian; Hanandyo Dardjito; Azim Abdurakhmanovich Yuldashev; Sri Murlianti; Eri Ester Khairas; Lukman Handoko; Ihwana As'ad (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
This research aims to evaluate the impact of education decentralization through the local curriculum in improving senior secondary school students' vocational and economic skills. This research uses a mixed methods approach with a sequential exploratory design. This design applied a qualitative approach followed by a quantitative approach. Data collection with the qualitative approach used in-depth interviews, while the quantitative approach used questionnaires and documentation of practical exam results. The participants in the qualitative approach were the vice principal and the traditional cookery subject teacher. The sample in the quantitative approach was students who took traditional cookery subjects. Qualitative data analysis used the Miles and Huberman formula, namely data display, data reduction, and conclusions, while quantitative data analysis used descriptive quantitative and MANOVA. The results showed that the impact of decentralization through the local content curriculum on improving students' vocational and economic skills was in the